Reverse polarity optical Orthogonal frequency Division Multiplexing for High-Speed visible light communications system - Ghaida Muttashar Abdulsahib; Dhana Sekaran Selvaraj; A. Manikandan; SatheeshKumar Palanisamy; Mueen Uddin; Osamah Ibrahim Khalaf; Maha Abdelhaq; Raed Alsaqour (Egyptian Informatics Journal, 2023)
The radio frequency spectrum, which has been steadily getting smaller, is under pressure from growing cellular data traffic. A more dependable communication channel is required. To setup the communication medium, VLC uses LED illumination. In order to increase network throughput, the goal of this study is to analyze and model signal conditioning techniques in the visible spectrum. VLC technology offers synchronized illumination of LED lamps as well as wireless broadband connectivity. Using the real-valued O-OFDM baseband signal, optical orthogonal frequency division multiplexing (O-OFDM) offers a viable modulation option for very-low-bit-rate (VLC) systems to modulate the optical carrier's instantaneous power to attain gigabit data rates. However, one important design difficulty preventing VLC from being commercialized is how to combine industry-favored pulse width modulation (PWM) dimming technology while retaining a dependable, broadband connection. In this paper, Reverse Polarity optical orthogonal frequency division multiplexing (RPO-OFDM) is proposed as a new signal format for combining the fast O-OFDM contact signal with the comparatively slow PWM dimming signal, as both signals contribute to the illuminative brightness of the LED. The average SNR, additional testing demonstrates that the suggested method outperforms the Asymmetrically clipped optical OFDM (ACO), Optimized Flipped Optical (OFO) and DC biased optical OFDM (DCO), and algorithms in similar operating conditions.